A rat model of placental inflammation explains the unexplained elevated maternal serum alpha‐fetoprotein associated with adverse pregnancy outcomes. Issue 10 (5th August 2019) - Hu, Jilin; Zhang, Jinman; Chan, Ying; Zhu, Baosheng
Abstract: Aim: It has been reported in numerous studies that elevated maternal serum alpha‐fetoprotein (MS‐AFP) is associated with adverse pregnancy outcomes (APO), such as pre‐eclampsia, stillbirth, preterm birth and fetal growth restriction. However, the mechanism linking elevated MS‐AFP and APO is obscure. In this study, we tried to explore the mechanism by using pregnant rats. Methods: Lipopolysaccharide (LPS) was used to induce placental inflammation in pregnant rats. Maternal serum and placental inflammatory cytokines and placental morphology were used to assess the level of placental inflammation. The incidences of APO and the levels of MS‐AFP were evaluated. The expressions of alpha‐fetoprotein (AFP) in the related organs and fetal serum AFP levels were detected. Results: Compared to saline‐treated pregnant rats, LPS led to elevated maternal serum and placental inflammatory cytokines and a higher rate of placental inflammation. Lipopolysaccharide resulted in the features of APO and at the same time elevated MS‐AFP. Maternal serum alpha‐fetoprotein levels were significantly correlated to the evaluation parameters of APO. Lipopolysaccharide did not increase the expressions of AFP in fetal liver, maternal liver and placenta, but reduced the fetal serum AFP levels. Conclusion: The phenomenon that elevated MS‐AFP is associated with APO, which has been reported in human pregnancies, is observed in our rat model. Placental inflammation can be the potential cause linking the two manifestations together. Although the source of elevated MS‐AFP is not identified, fetal blood circulation is suspected. Our study may provide an animal model for the future studies on this subject.